Perspective Response of Climate Change Impacts on Agricultural Crops in Sauraha-Pharsatikar VDC, Rupandehi District, Nepal - Khanal, Kapil; Khanal, Subodh; Dhungana, Surya Mani (International Journal of Applied Sciences and Biotechnology, 2017)
A survey research was conducted in Sauraha-Pharsatikar VDC of the Rupandehi district to study the perspective response of the farming communities on the impacts of the climate change in agricultural crops. Primary information was collected from household survey by administering pre-tested questionnaire and necessary data were collected from National Wheat Research Project (NWRP), Bhairahawa. Several results are obtained on the recall basis of the respondents thus they can not assumed correctly and all the past information provided by the farmers cannot be cross checked due to the lack of sufficient and reliable system for recording and checking. The trend analysis of rainfall data of Bhairahawa of 30 years (1984-2013) showed that the pattern of rainfall was irregular and it was in a decreasing trend by 1.944 mm per year and average maximum temperature has increased by 0.0.15oC and average minimum temperature has increased by 0.0.61oC per year which justifies that the summers are growing hotter and winters are growing warmer. About 52% of the respondents suggested monsoon starts earlier, 85% suggested there is more intense rain during the monsoon and 91.75% suggested drought has increased. 98.33% of the respondents perceived that the summer has become hotter. In general there is increase in the yield of cereal crops whereas the yield of pulses, legumes and vegetables had declined. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 345-355